FACTORS RELATED TO PEAK EXPIRATORY FLOW RATE IN PULMONARY TUBERCULOSIS PATIENTS - Wulandari, Shenda Maulina; Hijriyati, Yoanita; Sabina, Shalsa (Faculty of Nursing and Midwifery, Binawan University, 2024)
Patients with pulmonary tuberculosis can be at risk of bronchial obstruction due to secretions or secretions that collect and shallow breathing due to pain, which can cause atelectasis and decreased Peak Expiratory Flow Rate (PEFR) in pulmonary TB patients. The purpose of this study was to determine the relationship between PEFR in pulmonary TB patients at the Kramat Jati Health Center. This type of research uses correlation analytic observation using cross-sectional design and data analysis using Chi Square and Sperman rank methods. The sample in this study were 50 respondents at the TB Poly Kramat Jati Health Center and were collected using total sampling. Conclusion: The results of this study showed that gender was associated with PEFR in pulmonary TB patients with a p value=0.016 p <0.05 and work was associated with PEFR in pulmonary TB patients with a p value=0.007 p <0.05, age was unrelated to PEFR in pulmonary TB patients with a p value=0.412 and so was BMI with a p value=0.509. Suggestion: for more in-depth matters related to PEFR in pulmonary TB patients can be seen in terms of environmental factors or the physical condition of the patient.